TransCulture : lA Biennale di Venezia 1995. - XLVI La Biennale di Venezia, 1995; Friis-Hansen, Dana; Fukutake, Soichiro; Imafuku, Ryuta; Mesquita, Ivo; Nanjo, Fumio; Poshyananda, Apinan; Quittner, Joshua (Tokyo : The Japan Foundation, 1995)
Bennett, Gordon ; Bruly-Bouabré, Frédéric ; Cai Guo-Qiang ; Chong, Ping ; Gill, Simryn ; Grigely, Joseph ; Kohmura, Masao ; Mootoo, Shani ; Murakami, Takashi ; Neshat, Shirin ; Juliet, Reamillo and ; Technocrat ; Varejao, Adriana ; Party, World Tea ; Yung, Rene
biografie
XLVI Biennale di Venezia, 1995, TransCulture, June 11 - September 4, 1995
Engels & Japans
kunstcatalogus